The People Perception of Waste Management in Malaysia - Melly, Shinta; Azman, Nur Syafawani Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
Abstract Perception in relation to environment, which is process by individuals organize and interpret the impression of their senses to give meaning to their environment. With the perception, attitude will be formed which stable tendency to act in certain situations. The purpose of this study is to find out the perception of the people in Malaysia towards to waste management which seen from the role of the people in waste management, the motivation of the people to participate and the activities of people participation in waste management. This type of research is descriptive qualitative using observation, interview, and documentation study techniques in data collection. The results of the analysis of this study are: a) public perception of waste management in Malaysia b) efforts made by the government in relation to waste management in Malaysia c) impact of increasing waste production in Malaysia. Kata Kunci : Waste, Perception, Waste Management